The Rooming Houses of Furby Street - Maunder, Mike; Burley, David (Institute of Urban Studies, 2008)
50 p. This magazine is part of a much larger historical study, Living on Furby, Narratives ofHome. The larger study is a detailed history of one block of Furby, between Portage and Broadway, from its beginnings to the present day. This magazine extracts and elaborates material from the main study to focus on one aspect of the block's history- rooming houses. The understanding of rooming houses on the block has changed throughout its history, from a commonly accepted and respectable way of life in the block's first century, to a way of warehousing low-income people in substandard housing in the last 20 years. To show this change, the history of the block is divided into four periods: BEGINNINGS --First Nations times to the Forties ROOMING "HOMES" --The Forties to the Seventies. POVERTY --The Seventies to 2003 REVITALIZATION -- 1996 to 2008 Each period is described with three to five chapters. These chapters tell the stories of many people who lived,in the houses. Their stories are placed in the wider context of historical events and·trends in the city and the country. At the end of each period, there is a brief discussion of some historical themes which we encountered as we did this research. These discussions include an explanation of how the research was conducted. We hope these discussions and explanations might encourage and assist individuals and community groups who want to undertake similar historical research. This magazine focuses on the rooming houses on Furby. But there is much more to the history of this block than simply rooming houses. The broader and more complex history can be found in the main historical study: Living on Furby, Narratives of Home, Winnipeg, Manitoba, 1880 - 2005, University of Winnipeg, 2008 http://ius.uwinnipeg.ca/WIRA/wira_publications.htm Winnipeg Inner-City Research Alliance